ANALISIS BIBLIOMETRIK TREN PUBLIKASI PENDEKATAN STEM BERBASIS COMPUTATIONAL THINKING DALAM PEMBELAJARAN MATEMATIKA - Vita Nova Anwar; Tatang Herman (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research was a bibliometric study that aims to identify journals about STEM computational thinking approaches in mathematics learning. Research data was collected by analyzing journals from 2017-2021. Data analysis stages (1) journals are taken from the Scopus and dimension databases (2) journals are filtered through Microsoft excel (3) Checking the completeness of each journal through the mendeley application (4) displaying bibliometric analysis using Vos Viewer. The results show that the trend of STEM Computational Thinking research is based on collaboration between authors. The results also show the limitations of journal publications related to the STEM approach and computational thinking in mathematics learning. This is an opportunity for researchers to study STEM computational thinking in mathematics learning.